Examining School Social Work Certifications across the Midwest States - Robert Lucio; Emilie Souhrada; Julie Inciti; Brandon Mitchell (International Journal of School Social Work, 2024)
School social workers are increasingly being recognized and employed in schools across the country to promote critical avenues of system-wide school-based support. However, limited research has explored state certification standards of school social workers to understand the implications on practice efficacy and roles to improve the overall capacity of practitioners. In this study, we examine licensing standards and practice across 13 Midwest states, leveraging key partners in each state of interest. Findings reveal a large variation in SSW preparation, certification, and licensing standards. Aspects discussed in the results include, degree requirements, preparation programs, state endorsement, pathways to licensure, evaluation components, board of education requirements, and direct service implications. We discuss the implications of our findings and delineate the complexities, inconsistencies, and outline strategies for future research. As schools increasingly come to rely and depend on school social workers, we must work to build consistency in state requirements, solidify training standards, and strive to build efficacy and strength of the field.
Keywords: School social worker; certification standards; preparation; licensing; practice; roles